Educating at scale: sustainable library learning at the University of Melbourne. Issue 3 (14th March 2016) - Phillips, Andrea
Abstract : Purpose: – Most libraries in higher education are facing the challenge of providing valued and improved services with the same or fewer resources. Focussing on the library learning service at one university, the purpose of this paper is to consider how libraries can find new service models with contracting resources while aligning with institutional and professional values and providing value-in-use for end users and key stakeholders. Design/methodology/approach: – Following a discussion of sustainability as relevant to library services, the paper presents a case study of one library's approach to sustaining its library learning service. Findings: – The sustainability of library services is aided by developing a service blueprint that provides direction and structure yet is dynamic and responsive. To be successful the approach should be grounded in resource realities, encourage scalability where possible and address the values and needs of key stakeholders. Originality/value: – The paper presents a workable, integrated approach to managing a library learning service so that it delivers value and is sustainable.